Inheritance of resistance to root-lesion nematodes (Pratylenchus thornei and P. neglectus) in five doubled-haploid populations of wheat - Thompson, John P.; Rebecca S. Zwart; Butler, David (Euphytica, 2012)
Nematode species Pratylenchus thornei and P. neglectus are the two most important root-lesion nematodes affecting wheat (Triticum aestivum L.) and other grain crops in Australia. For practical plant breeding, it will be valuable to know the mode of inheritance of resistance and whether the same set of genes confer resistance to both species. We evaluated reactions to P. thornei and P. neglectus of glasshouse-inoculated plants of five doubled-haploid populations derived from five resistant synthetic hexpaloid wheat lines, each crossed to the susceptible Australian wheat cultivar Janz. For each cross we determined genetic variance, heritability and minimum number of effective resistance genes for each nematode species. Distributions of nematode numbers for both species were continuous for all doubled-haploid populations. Heritabilities were high and the resistances were controlled by 4-7 genes. There was no genetic correlation between resistance to P. thornei and to P. neglectus in four of the populations and a significant but low correlation in one. Therefore, resistances to P. thornei and to P. neglectus are probably inherited quantitatively and independently in four of these synthetic hexaploid wheat populations, with the possibility of at least one genetic factor contributing to resistance to both species in one of the populations. Parents with the greatest level of resistance will be the best to use as donor parents to adapted cultivars, and selection of resistance to both species in early generations will be optimal to carry resistance through successive cycles of inbreeding to produce resistant cultivars for release.
Keywords: Aegilops tauschii; Disease resistance; Durum wheat; Germplasm development; Triticum aestivum; Wheat breeding